y(кас) = f'(x0) (x - x0) + f(x0)
f'(x) = 2x/3
f'(x0) = 2/3
f(x0) = 1/3
y(кас) = 2x/3 - 2/3 + 1/3 = 2x/3 - 1/3
1) a(n) = 9 - 3n
a1 = 9 - 3 × 1 = 9 - 3 = 6
a8 = 9 - 3 × 8 = 9 - 24 = -15
2) S(n) = (a1 + a(n))/2 × n => S8 = (a1 + a8)/2 × 8
S8 = (6 - 15)/2 × 8 = (-9 × 8)/2 = -9 × 4 = -36
Ответ: сумму первых восьми членов арифметической прогрессии равна -36.
<span>600+320 000 - 20 000=320 600-20 000=300 600
</span><span>150 000-100 000 +9 000=50 000 +9000=59 000
</span><span>37000-30 000 +400 000=7000+400 000=407 000
5900 000 +300-9000 000=5 900 300-9 000 000 =</span><span>-84099700</span>
Подставим в числитель и знаменатель х=0 и получим
=lim
=lim